DEVELOPING A CULTURE OF COLLABORATION IN THE OPERATING ROOM: MORE THAN EFFECTIVE COMMUNICATION - Wade, Patricia (Operating Room Nurses Association of Canada Journal, 2014)
The purpose of this literature review was to examine the current state of knowledge on successful collaborative practice in the operating room. Using the determinants of successful collaborative practice, developed by San-Martin-Rodriguez, Beaulieu, D’Amour, & Ferrada-Videla,6 the current literature on collaboration in the operating room was reviewed in order to identify the gaps in knowledge and identify future research avenues. The review highlighted that communication patterns among operating room team members was the most extensively researched aspect of teamwork. Other aspects, such as the willingness to engage in collaborative practice, trust, respect, societal factors, and cultural factors, were absent from the literature. Future research will need to focus on these gaps in knowledge in order to maximize our limited research resources and improve patient safety.